Structural analysis and development of a short form of the Test Anxiety Inventory – Spanish version (TAI-S) in college students from Lima - Dominguez-Lara, Sergio (2017)
The aim of the present study is to examine the internal structure of the Test Anxiety Inventory-Spanish version (TAI-S) and have a brief version. It was assessed of a sample of 376 Peruvian university students (73.1% women) between 16 and 55 years old (M = 20.71). The internal structure of TAI-S was analyzed by using structural equation modeling (factorial confirmatory analysis) and the short version was obtained on the basis of a Bifactoral model and conceptual approaches. Four models were evaluated: orthogonal, oblique, bifactor and one-dimensional. As the result, the TAI-S is constituted by a single dimension. Likewise, the short version shows robust indicators and based on the empirical evidence with the long version. Finally, the two versions showed reliability coefficient with high magnitudes. In conclusion, the two version studied show favorable psychometric properties that support its use in the Peruvian context.